Utilization of the RSA Algorim in Business Communication in Making e-Commerce Applications - Fauzi, Fauzi; Fachry, Muhammad (Al'Adzkiya, 2020)
Cryptography is a science or art of securing messages and is carried out by cryptographers. Data that is secured includes several aspects such as message security such as confidentiality, data integrity, and authentication. One cryptographic algorithm that is often used in the process of data security is the RSA algorithm. RSA is short for the names of the inventors of this algorithm, namely Ron, Shamir and Adleman. RSA is an algorithm that uses the concept of public key creation (the asymmetry / key used to encrypt is different from that used to decrypt). Where the applications made with Webbase in their security are still often using the MD5 and Sha algorithms so that additional security is needed in securing the existing education in making e-Commerce. Keyword : RSA, Business, Communication, e-Commerce.